2022
DOI: 10.1111/epi.17455
|View full text |Cite
|
Sign up to set email alerts
|

De novo KCNA6 variants with attenuated KV1.6 channel deactivation in patients with epilepsy

Abstract: Objective: Mutations in the genes encoding neuronal ion channels are a common cause of Mendelian neurological diseases. We sought to identify novel de novo sequence variants in cases with early infantile epileptic phenotypes and neurodevelopmental anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In addition, gain‐of‐function mutations of Kv1.1 have been reported, including the drug‐resistant Kv1.1‐L 296 F mutation in the VSD we consider here as well as a Kv1.1‐A 261 T mutation in the S3 transmembrane segment that causes mild, drug‐responsive, focal epilepsy in patients 8 . Recently, gain‐of‐function mutations of Kv1.6 were found to be associated with neurodevelopmental disorders and seizures in patients 40 . Because Kv1.6 and Kv1.1 share high similarity in the pore region (Figure S3) and form heterotetrametric channels in the human brain, AETX‐K is anticipated to suppress excess current passed by these gain‐of‐function channels as well.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, gain‐of‐function mutations of Kv1.1 have been reported, including the drug‐resistant Kv1.1‐L 296 F mutation in the VSD we consider here as well as a Kv1.1‐A 261 T mutation in the S3 transmembrane segment that causes mild, drug‐responsive, focal epilepsy in patients 8 . Recently, gain‐of‐function mutations of Kv1.6 were found to be associated with neurodevelopmental disorders and seizures in patients 40 . Because Kv1.6 and Kv1.1 share high similarity in the pore region (Figure S3) and form heterotetrametric channels in the human brain, AETX‐K is anticipated to suppress excess current passed by these gain‐of‐function channels as well.…”
Section: Discussionmentioning
confidence: 96%
“…8 Recently, gain-of-function mutations of Kv1.6 were found to be associated with neurodevelopmental disorders and seizures in patients. 40 Because Kv1.6 and Kv1.1 share high similarity in the pore region (Figure S3) and form heterotetrametric channels in the human brain, AETX-K is anticipated to suppress excess current passed by these gain-of-function channels as well. The increased K + currents likely lead to excess repolarization, and action potential shortening, disrupting the firing frequency and dampening neuronal excitability.…”
Section: Aetx-k Blocks Kv11-kv12 Heterotetrameric Channelsmentioning
confidence: 99%
“…Raw data were processed and filtered with established pipelines at diagnostic or research laboratories as described previously. 9 , 10 , 11 , 12 Variant (single nucleotide and indel) calling and filtering was performed using the Genome Analysis Tool Kit (GATK). Variants that did not adhere to the following criteria were excluded from further analysis: allele balance of >0.70, QUAL of >20, and coverage of >20×.…”
Section: Methodsmentioning
confidence: 99%
“…The Kv1.6 channel is encoded by the gene KCNA6 . A recent study identified de novo gain-of-function mutations in KCNA6 in patients with epilepsy [ 57 ]. Mutant Kv1.6 channels display slowed channel closing time and a negative shift in deactivation voltage.…”
Section: Ion Channel Gene Mutations That Cause Ataxiamentioning
confidence: 99%